Assessment of the sleep parameters in patients with obstructive sleep apnea syndrome with a history of traffic accident. Issue 2 (2013) - Abakay, Özlem; Şen, Hadice Selimoğlu; Taylan, Mahşuk; Sezgi, Cengizhan; Tanrıverdi, Mehmet Halis; Tanrıkulu, Abdullah Çetin; Abakay, Abdurrahman; Kırbaş, Gökhan
No abstract available